Prioritizing Declared Religion over Believed Religion: Christian Youth and Two Conflicting Narratives of Lived Religion in South India - Mocherla, A. (University of jaffna, 2024)
This essay attempts to critically examine the notion of ‘declaration of faith’ in the contemporary South Indian socio-political context, primarily to analyze and bring forth new patterns of social conflict between ‘believed religion’ and ‘declared religion’ in the process of raising Christian testimony among youth on University/College campuses. With that premise, it looks at how the State declared religious identity could effectively undermine the personal religious convictions of individuals and social groups, in this particular case the Dalit Christians, when minority religious institutions and organizations tend to transform themselves into subordinate bureaucratic structures of the State. Further, it also explores how the essentializing aspects of identity tend to defeat the social aspirations of individuals/social groups by transforming the imposed boundaries of identity, identity politics, and associated stereotypical perceptions into active sources of internal social conflict in a faith-based student organization. Central arguments of this paper are largely informed and guided by empirical field-data collected from the coastal Andhra Pradesh, South India.
Keywords: Declaration of faith; Dual religious identity; Dalit christianity; Lived religion; Gospel of liberation; Christian testimony